Reduction in C-Peptide Levels and Influence on Pharmacokinetics and Pharmacodynamics of Insulin Preparations: How to Conduct a High-Quality Euglycemic Clamp Study - Tao, Yi; Zhu, Mingxue; Pu, Junliang; Zhang, Peilin; Wan, Lei; Tang, Chengyong (Frontiers in Pharmacology, 2021)
Objective: To investigate the reducing of C-peptide in the euglycemic clamp study and its effect on evaluation of insulin bioequivalence, determine the best reducing range of C-peptide. Methods: 39 healthy Chinese male volunteers were enrolled and underwent a single-dose, randomized euglycemic clamp, who were injected subcutaneously with insulin glargine (0.4iu/kg). Blood samples were collected predose and up to 24h postdose to assess pharmacokinetics (PK) and C-peptide. Pharmacodynamics (PD) was assessed by euglycemic clamp lasting up to 24 h. Results: We divided volunteers into three groups according to the reducing extent of C-peptide, group A(ratio of C-peptide reduction ＜0.3, N=13), group B(0.3≤ratio of C-peptide reduction ＜0.5, N=15) and group C(ratio of C-peptide reduction≥0.5 , N=11), there were significant differences in three groups(P=0.000). The upper and lower limit of blood glucose oscillation in group C was statistically lower than the other groups, the glucose oscillating range of group C was -17.0%±6.6% to -1.1%±6.7%. AUC0-24h in group A, B and C were 9.7±2.2, 11.0±2.9.11.9±2.1 ng/ml×min respectively, which showed an increasing trend in three groups (P trend=0.041). For quality assessment, Average glucose (P=0.000) and MEFTG (P =0.001) in three groups were significantly different. Conclusion: The extent of C-peptide reduction will affect PK/PD of insulin preparation and quality of euglycemic clamp. Moreover, the ratio of C-peptide reduction should be better higher than 50%, correspondingly, the blood glucose regulation range in euglycemic clamp is better keeps in -10% to 0.